(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2013)
The Concept Reader launch was delivered in what we may one day view as a time of great social upheaval. Many widely held values and rights are being challenged by the Conservative-led neoliberal agenda of austerity. In our communities of place, interest and practice we now need to come together, debate and organise. With the launch, Ian Fyfe and Stuart Moir provided us with a platform to think critically and creatively about the current direction of youth work and our ability to influence it.